Acute chest pain: nurses challenging a time-dependent pathology at the hospital entrance doors - Angélica Zanettini; Marisa Basegio Carretta; Gabriela Stochero; Juliane Christofari da Silva; Camila Marcon; Viviane Pecini da Cunha (Universidade Federal de Santa Maria, 2020)
Objective: to assess the perception of nurses in the face of patients with chest pain at the entrance doors of the Urgent and Emergency Service in a general hospital. Method: exploratory and descriptive study, with a qualitative approach, carried out with 10 nurses in a large general hospital in Rio Grande do Sul, in 2018. Data collection occurred through semi-structured interviews, studied according to content analysis. Results: there were difficulties in understanding the Risk Classification, structural and organizational issues, besides the lack of qualified professionals. As for potentialities, care in a quick way, seeking the most correct identification of the signs presented by the patient and the accomplishment of the electrocardiogram in the appropriate time. Conclusion: it was evidenced that the nurse perceives to be able to make quick and accurate decisions through the knowledge of care protocols. Nevertheless, there is interference from processes such as undersizing of personnel and the excessive demand for entrance door services.